From symbolic inclusion to shared governance: contesting conservation in a climate-stressed South African landscape - Maphosa, Mandlenkosi; Effossou, Kablan Antoine; Moyo, Philani (Frontiers in Sustainability, 2025)
Conservation areas are increasingly seen as crucial for addressing biodiversity loss and climate change, yet their expansion often produces socio-economic tensions with adjacent communities, particularly where governance is exclusionary. This study examines perceptions of equity, resource access, and governance among rural communities and private game reserve officials in the Makana Local Municipality, Eastern Cape, South Africa. It also investigates how climate variability intensifies these challenges by deepening local vulnerability. Guided by vulnerability and participatory governance theory, the study adopted a qualitative, interpretivist approach. Data were collected between July and August 2024 through 58 in-depth interviews with community members, 2 focus group discussions and 5 key informant interviews with conservation managers and community leaders. The study focused on communities surrounding Amakhala and Lalibela Game Reserves, including Alicedale, Seven Fountains, and Kraabos. Findings reveal that while some benefits from conservation exist—such as employment and limited outreach, these are perceived as symbolic, precarious, and inequitably distributed. Communities report restricted access to land, water, and sacred sites, with governance processes experienced as opaque and exclusionary. Climate variability, particularly erratic rainfall and drought, exacerbates these vulnerabilities by undermining agricultural livelihoods and intensifying resource scarcity. The study concludes that socially just and climate-resilient conservation in South Africa requires a shift from rhetorical inclusion to meaningful participation, transparent governance, and equitable benefit-sharing. Aligning conservation with local rights, needs, and adaptive capacities is essential for enhancing both biodiversity protection and community resilience.